Erythrocyte osmotic fragility is not linked to vitamin C nutriture in adults with well-controlled type 2 diabetes - Lundy, Ciara; Fessler, Samantha N.; Johnston, Carol S. (Frontiers in Nutrition, 2022)
Erythrocyte fragility is amplified by oxidative stress and linked to diabetes-specific microvascular disease. Vitamin C supplementation improves glycemic indices in adults with type 2 diabetes (T2D) by improving antioxidant status. This cross-sectional study examined the relationships between vitamin C status and erythrocyte osmotic fragility in adults with or without T2D. Participants provided a fasting blood sample for erythrocyte osmotic fragility testing as a function of hypotonic NaCl concentrations. Additionally, plasma was stabilized with metaphosphoric acid prior to vitamin C analysis using isocratic reverse-phase UV-HPLC separation. Participants were grouped as diagnosed T2D (n=14; 36% female; 55.5±8.2 y; 31.5±9.0 kg/m2; HbA1c: 7.4±1.9%; plasma vitamin C: 36.0±12.2 μM) or no diabetes (n=16; 69% female; 38.7±13.5 y; 26.8±6.6 kg/m2; HbA1c: 5.4±0.3%; plasma vitamin C: 34.8±10.9 μM). Participant characteristics differed between groups only for age and hemoglobin A1c (HbA1c) (p<0.05). All hemolysis parameters were in normal ranges for the participants with T2D, and no significant differences in hemolysis parameters were noted between those with or without T2D. However, among participants with T2D, the NaCl concentration eliciting 50% hemolysis was higher for those with low (<7%) versus high (>7%) HbA1c values (p=0.037) indicating a slightly higher erythrocyte fragility in the former group. Vitamin C status did not impact any of the hemolysis parameters in adults with or without T2D. Thus, erythrocyte fragility was not elevated in T2D, and vitamin C nutriture was not related to erythrocyte fragility in adults with well-controlled T2D.